Application of the First Come First Served Method in the Mobile-Application System - Muhammad Andi Syaifullah; Lilis Nur Hayati; Lutfi Budi Ilmawan (Komunitas Dosen Indonesia, 2025)
Royal Cafe Makassar still relies on a manual system for managing queues and processing orders, which leads to long waiting lines, delayed service, and frequent recording errors. This study aims to design and implement a mobile-based queue management application using the First Come First Served (FCFS) method to create a more efficient, structured, and transparent ordering process. System development follows the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and maintenance phases. The application provides features for registration and login, digital menu browsing, ordering, payment processing, queue monitoring, and a role-based workflow involving administrators, baristas, and waiters. Functional validation is conducted using black-box testing, while usability evaluation employs the System Usability Scale (SUS). The results show that every major function of the application operates according to the specified requirements. The SUS evaluation, involving 73 respondents, yields an average score of 82.35, which falls into the “very good” and “acceptable” categories, indicating high usability and user satisfaction. The FCFS mechanism effectively addresses operational issues by ensuring fair and consistent service order based on customer arrival time, reducing manual workload, and minimizing ordering errors. Overall, the developed system provides a practical digital solution for improving café service efficiency and can serve as a reference model for similar small-scale businesses adopting queue management applications.